2021
DOI: 10.1080/20008198.2021.1943188
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention with eye movement desensitization and reprocessing (EMDR) therapy to reduce the severity of post-traumatic stress symptoms in recent rape victims: a randomized controlled trial

Abstract: Background About 40% of rape victims develop post-traumatic stress disorder (PTSD) within three months after the assault. Considering the high personal and societal impact of PTSD, there is an urgent need for early (i.e. within three months after the incident) interventions to reduce post-traumatic stress in victims of rape. Objective To assess the effectiveness of early intervention with eye movement desensitization and reprocessing (EMDR) therapy to reduce symptoms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 51 publications
0
39
0
1
Order By: Relevance
“…Two recent systematic reviews and meta-analyses identified 17 published studies on different early interventions after sexual assault to prevent PTSD and other mental health disorders [ 17 , 18 ]. The interventions included video interventions [ 19 ], psychoeducation and cognitive behavioral strategies [ 20 ], and EMDR [ 21 ]. The effect sizes in reducing post-traumatic stress symptoms were in the small-to moderate range [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent systematic reviews and meta-analyses identified 17 published studies on different early interventions after sexual assault to prevent PTSD and other mental health disorders [ 17 , 18 ]. The interventions included video interventions [ 19 ], psychoeducation and cognitive behavioral strategies [ 20 ], and EMDR [ 21 ]. The effect sizes in reducing post-traumatic stress symptoms were in the small-to moderate range [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to eliminate this factor studies with true experimental research design or quasi-experimental research design studies needs to be done. Covers et al (2021) found out that there is no difference in the watchful waiting group who provided psychoeducation and emotional support and two sessions of EMDR therapy group in reducing post traumatic symptoms, depression, sexual dysfunction, feelings of guilt and shame in the rape victims. Our findings should be supported more by randomized controlled trials with control groups.…”
Section: Discussionmentioning
confidence: 95%
“…However, a recent randomized controlled trial (RCT) on adult victims of rape, who sought help from a Sexual Assault Centre, studied the effectiveness of two sessions of EMDR therapy in comparison to watchful waiting. The results showed that early EMDR interventions were no more effective than watchful waiting in reducing post-traumatic stress symptoms (Covers et al, 2021 ). Roberts, Kitchiner, Kenardy, and Bisson ( 2009 ) suggested that early psychological interventions should only be recommended for those who meet the threshold for a clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%